(untitled) (Journal of Comparative & International Higher Education, 2024)
In 2023, China leads the world in the number of Open Online Courses (OOC, over 64500) and learners (over 1.88 billion). In this article, we provide a brief review of the development of OOCs in China and outline the current situation of Chinese OOC focusing on learning platforms, course size and structure, and micro-credential courses. We also summarize the development and application of OOC in China focusing on national policy guidance, the organizational structure of OOCs, different modes of OOC development, and the establishment of a standardized quality assurance system. We also discuss the OOC credit recognition, blended learning, and multi-school collaborative teaching. Finally, we consider the future development trend of OOCs in China from the perspective of improving digital teaching literacy of instructors and expanding international exchange and cooperation.